Recurrent heart failure hospitalizations increase the risk of cardiovascular and all‐cause mortality in patients with heart failure in Sweden: a real‐world study. (9th March 2021) - Lindmark, Krister; Boman, Kurt; Stålhammar, Jan; Olofsson, Mona; Lahoz, Raquel; Studer, Rachel; Proudfoot, Clare; Corda, Stefano; Fonseca, Ana Filipa; Costa‐Scharplatz, Madlaina; Levine, Aaron; Törnblom, Michael; et al.
Abstract: Aims: Heart failure (HF) is a leading cause of hospitalization and is associated with high morbidity and mortality. We examined the impact of recurrent HF hospitalizations (HFHs) on cardiovascular (CV) mortality among patients with HF in Sweden. Methods and results: Adults with incident HF were identified from linked national health registers and electronic medical records from 01 January 2005 to 31 December 2013 for Uppsala and until 31 December 2014 for Västerbotten. CV mortality and all‐cause mortality were evaluated. A time‐dependent Cox regression model was used to estimate relative CV mortality rates for recurrent HFHs. Assessment was also done for ejection fraction‐based HF phenotypes and for comorbid atrial fibrillation, diabetes, or chronic renal impairment. Overall, 3878 patients with HF having an index hospitalization were included, providing 9691.9 patient‐years of follow‐up. Patients were relatively old (median age: 80 years) and were more frequently male (55.5%). Compared with patients without recurrent HFHs, the adjusted hazard ratio (HR [95% confidence interval; CI]) for CV mortality and all‐cause mortality were statistically significant for patients with one, two, three, and four or more recurrent HFHs. The risk of CV mortality and all‐cause mortality increased approximately six‐fold in patients with four or more recurrent HFHs vs. those without any HFHs (HR [95% CI]: 6.26 [5.24–7.48] and 5.59 [4.70–6.64], respectively). Similar patterns were observed across the HF phenotypes and patients with comorbidities. Conclusions: There is a strong association between recurrent HFHs and CV and all‐cause mortality, with the risk increasing progressively with each recurrent HFH.